Phylogenetic Analysis of Mitochondrial Genome of Tabanidae (Diptera: Tabanidae) Reveals the Present Status of Tabanidae Classification - Mingyue Liu; Tingting Wu; Hao Ju; Xiaoxiao Ma; Zihao Fang; Qiaocheng Chang (Insects, 2022)
Tabanidae suck the blood of humans and animals, are important biological vectors for the transmission of diseases, and are of considerable economic and medical significance. However, current knowledge about the mitochondrial genome of this family is limited. More complete mitochondrial genomes of Tabanidae are essential for the identification and phylogeny. Therefore, this study sequenced and analyzed six complete mitochondrial (mt) genome sequences of four genera of Tabanidae for the first time. The complete mt genomes of the six new sequences are circular molecules ranging from 15,851 to 16,107 base pairs (bp) in size, with AT content ranging from 75.64 to 77.91%. The six complete mitochondrial genomes all consist of 13 protein-coding genes (PCGs), 2 ribosomal RNA genes (RRNA), 22 transfer RNA genes (tRNAs), and a control region, making a total of 37 functional subunits. ATT/ATG was the most common start codon, and the stop codon was TAA of all PCGS. All tRNA except tRNA Ser1 had a typical clover structure. Phylogeny was inferred by analyzing the 13 concatenated amino acid sequences of the 22 mt genomes. Bayesian inference, maximum-likelihood trees, and maximum-parsimony inference analyses all showed consistent results. This study supports the concept of monophyly of all genus, ratifies the current taxonomic classification, and provides effective genetic markers for molecular classification, systematics, and genetic studies of Tabanidae.